2014
DOI: 10.1163/15691330-12341332
|View full text |Cite
|
Sign up to set email alerts
|

Microaggression and Moral Cultures

Abstract: Campus activists and others might refer to slights of one's ethnicity or other cultural characteristics as "microaggressions," and they m ight use various forums to publicize them . Here we exam ine this phenom enon by drawing from Donald Black's theories of conflict and from cross-cultural studies of conflict and morality. We argue th a t this behavior resembles other conflict tactics in w hich the aggrieved actively seek the sup port of third parties as well as those th a t focus on oppression. We identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 61 publications
0
65
0
5
Order By: Relevance
“…In an age that is increasingly characterized by emphasis on victim inclusion, political correctness, and microaggressions (Campbell and Manning 2014), our findings provide insight into the more subtle ways in which third parties may react to a victim of sexual violence. Whereas Javaid (2015b, p. 275) concluded that Bfeminizing or gendering victimization is mostly seen within labels that are derogatory …, pussies, sissies … and so on,^respondents in the current study feminized the victim in ways that resulted in the attribution of more positive traits and less negative traits.…”
Section: Practice Implicationsmentioning
confidence: 86%
“…In an age that is increasingly characterized by emphasis on victim inclusion, political correctness, and microaggressions (Campbell and Manning 2014), our findings provide insight into the more subtle ways in which third parties may react to a victim of sexual violence. Whereas Javaid (2015b, p. 275) concluded that Bfeminizing or gendering victimization is mostly seen within labels that are derogatory …, pussies, sissies … and so on,^respondents in the current study feminized the victim in ways that resulted in the attribution of more positive traits and less negative traits.…”
Section: Practice Implicationsmentioning
confidence: 86%
“…Oftentimes, people are accused of seeing oppression where there is none or making a big deal over a “small” action (Sue , ). In fact, much of the public discourse around microaggressions, particularly on college campuses, has turned in this direction, decrying that the focus on microaggressions reflects a new moral “culture of victimhood” (Campbell and Manning , 714–16) or “coddling” of people's emotions and intellectual exposure (Haidt and Lukianoff ). But the harm of microaggressions is not insignificant.…”
Section: Microaggressions and Their Harmmentioning
confidence: 99%
“…For example, on the positive valuation of suffering in Western tradition, see Nietzsche (1998). 12 We have, however, published an editorial elsewhere stating our commitment to academic freedom and preference for norms of dignity we believe conducive to that freedom (Campbell and Manning 2015a).…”
Section: Morality and Value-free Sociologymentioning
confidence: 99%
“…In December 2014 Comparative Sociology published "Microaggression and Moral Cultures" (Campbell and Manning 2014), in which we addressed the then-new phenomenon of university students and campus activists using online forums to publicize instances of so-called microaggressions -verbal slights and offenses that while individually minor and often unintentional were presented as evidence of the systematic oppression of minority groups. We described how aspects of the phenomenon corresponded to larger categories of conflict and social control, and how aspects of social structure explained why conflict and social control took on this form rather than some other.…”
Section: Introductionmentioning
confidence: 99%